Micro patterning of hydroxyapatite by soft lithography on hydrogels for selective osteoconduction. (November 2018) - Kiyama, Ryuji; Nonoyama, Takayuki; Wada, Susumu; Semba, Shingo; Kitamura, Nobuto; Nakajima, Tasuku; Kurokawa, Takayuki; Yasuda, Kazunori; Tanaka, Shinya; Gong, Jian Ping
Graphical abstract: Abstract: Mechanically robust hydrogels are promising biomaterials as artificial supportive tissue. These applications require selective and robust bonding of the hydrogels to living tissue. Recently, we achieved strong in vivo bone bonding of a tough double network (DN) hydrogel, a potential material for use as artificial cartilage and tendon, by hybridizing osteoconductive hydroxyapatite (HAp) in the gel surface layer. In this work, we report micro patterning of HAp at the surface of the DN hydrogel for selective osteoconduction. Utilizing the dissolution of HAp in an acidic environment, the soft lithography technique using an acid gel stamp was adopted to form a high-resolution HAp pattern on the gel. The HAp-patterned gel showed well-regulated migration and adhesion of cells in vitro . Moreover, the HAp-patterned gel showed selective and robust bonding to the rabbit bone tissue in vivo . This HAp soft lithography technique allows for simple and quick preparation of tailor-made osteoconductive hydrogels and can be applied to other hydrogels for selective bone bonding. Statement of Significance: Hydrogels, preserving large amount of water, have been studied for next-generation artificial soft tissues. However, fixation of hydrogels to living tissue was unsolved issue for clinical application. Recently, we achieved robust bonding of a tough double network gel to bone in vivo by coating of osteoconductive hydroxyapatite in the gel surface layer. For further progress for practical use, we report the micro patterning of HAp at the surface of the DN hydrogel by using soft lithography technique, to perform selective bonding to only objective area without unnecessary coalescence. The HAp lithography technique is simple, quick and non-toxic method to prepare tailor-made osteoconductive hydrogels and has universality of species of hydrogels.